Usher Syndrome: Case Reports of Two Siblings. - Prasad Sah, Raman; Gautam, Pragati; Baba Shrestha, Jyoti; Raj Joshi, Mahesh (Optometry & Visual Performance, 2015)
Background: Usher syndrome is a rare autosomal recessive disorder characterized by congenital sensory neural deafness and progressive visual loss secondary to retinitis pigmentosa. There are three different types of Usher syndrome. Retinitis pigmentosa is the main ophthalmic manifestation shared by all three. Differences in auditory and vestibular function are the distinguishing feature. Case Reports: Two brothers, 13 and 16 years of age, presented with chief complaints of progressive diminution of vision in both eyes, especially at night. They underwent a detailed evaluation which included dilated fundus examination, cycloplegic refraction, multifocal electroretinogram (mfERG), optical coherence tomography, visual evoked potential, and Goldmann perimetry. The evaluation revealed best corrected visual acuity of 6/12 and 6/9 in each case despite the presence of bony spicules and abolished mfERG amplitudes. The clinical findings supported the diagnosis of Usher syndrome Type I. Discussion: Early detection and intervention will help preserve residual vision in these cases.